Genius Envy Women Shaping French Poetic History, 1801-1900 - Paliyenko, Adrianna (Penn State University Press, 2016)
In Genius Envy Adrianna M. Paliyenko uncovers a forgotten past: the multiplicity and diversity of nineteenth-century French women's poetic voices. Conservative critics of the time attributed genius to masculinity and dismissed the work of female authors as "feminine literature." Despite the efforts of leading thinkers, critics, and historians to erase women from the pages of literary history, Paliyenko shows how female poets invigorated the debate about the origins of genius and garnered recognition in their time for their creativity and bold aesthetic ideas. This fresh account of French women poets' contributions to literature probes the history of their critical reception and considers the texts of celebrated writers such as Desbordes-Valmore, Ségalas, Blanchecotte, Siefert, and Ackermann. The results show that these women explicitly challenged the notion of genius as gendered, advocating for their rightful place in the canon.